Steam Reforming of methanol Over Cu/Al2O3/ZnO Catalysts - Somchai Akaratiwa; Tammanoon Odomman (ASEAN Journal of Chemical Engineering, 2003)
In this research, steam reforming of methanol over Cu/Al2O3/ZnO catalysts was investigated. The catalysts were prepared by conventional co-precipitation and  sequential precipitation methods. Especially, the sequential precipitation method were performed by varying the sequence of additions of copper, aluminum, and zinc nitrate solutions. The experimental results showed clearly that the preparation methods affected the performance of catalysts. The Cu/AI2O3/ZnO catalysts  prepared by consecutively adding copper, aluminum, and zinc nitrate solutionsexhibited better performance. The effect of Al2O3/ZnO molar ratios on the activity of catalysts was also studied. It was found that the catalysts with 50:5:45 of Cu/AI2O3/ZnO molar ratio showed higher activity than others. In order to improve catalytic activity, Mn- or Cr-promoted over Cu/Alp.jZnO was also investigated. It was interesting to observe that either the Mn- or the Cr-promoted Cu/AI2O3/ZnO catalysts have higher activity than nonpromoted ones, indicating that Mn and Cr promoters give some synergistic effect.